2018
DOI: 10.1001/jamapediatrics.2018.3030
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in the Use of Metabolic and Bariatric Surgery Among Pediatric Patients With Severe Obesity

Abstract: Severe pediatric obesity (class II or higher; body mass index [calculated as weight in kilograms divided by height in meters squared] ≥120% above the 95th percentile or ≥35) is a national public health crisis affecting more than 4.5 million children and adolescents in the United States. The prevalence of severe pediatric obesity has increased from 4.0% in 2000 to 6.0% in 2016. 1 For children and adolescents with this disease, metabolic and bariatric surgery (MBS) is effective in achiev ing long-term weight los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(23 citation statements)
references
References 7 publications
2
21
0
Order By: Relevance
“…Adolescents had a better response to SG than adults, which is consistent with previous studies (22,23). This is encouraging and supportive of the current trend of more frequent SG, with its reduced complexity and lower post-surgical prevalence of micronutrient deficiencies than RYGB, particularly in adolescents (18).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Adolescents had a better response to SG than adults, which is consistent with previous studies (22,23). This is encouraging and supportive of the current trend of more frequent SG, with its reduced complexity and lower post-surgical prevalence of micronutrient deficiencies than RYGB, particularly in adolescents (18).…”
Section: Discussionsupporting
confidence: 88%
“…A recent study showed greater resolution of T2D and HTN in adolescents as compared to adults after Roux-en-Y gastric bypass (RYGB) suggesting a benefit of early intervention (17). However, data comparing long-term outcomes following sleeve gastrectomy (SG), the most commonly performed MBS is not available (18). Moreover, data comparing outcomes of RYGB and SG across age are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Teen-LABS and associated ancillaries provide the most comprehensive prospectively collected data characterizing adolescent Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) outcomes, enhanced by ancillary inclusion of nonsurgical comparators. However, consistent with bariatric enrollment trends (2008-2012), 49 participants were predominantly White, female, and underwent RYGB. Understanding whether these findings generalize to females of other race/ethnic groups is important future research given known disparities for adverse sexual health outcomes.…”
Section: Discussionsupporting
confidence: 53%
“…According to the most recently available data from the NHANES, the prevalence of severe obesity from 2015 to 2016 was 1.9% among children and adolescents 2 to 19 years old, with 4.5% of adolescents age 16-19 years old affected by severe obesity (1). While strides have been made toward encouraging the utilization of metabolic and bariatric surgery (MBS) for pediatric patients with severe obesity, with definitive guidance from organizations such as the American Academy of Pediatrics (AAP) and the American Society of Metabolic and Bariatric Surgery (ASMBS) (14)(15)(16)(17), there remains a gap in care for patients who have been refractory to lifestyle modifications but do not meet criteria for MBS.…”
Section: Introductionmentioning
confidence: 99%